Changes in the tumor necrosis factor-α level after an ultrasound-guided femoral nerve block in elderly patients with a hip fracture - Jang,Ji Su (2018)
Abstract Background and objectives: An ultrasound guided femoral nerve block is an established analgesic method in patients with a hip fracture. Elevated cytokine levels correlate with poor patient outcomes after surgery. Hence, the aim of the study was to describe the levels of tumor necrosis factor-α after an ultrasound-guided femoral nerve block in elderly patients having a femoral neck fracture. Methods: A total of 32 patients were allocated into two treatment groups: 16 patients (femoral nerve block group; ultrasound-guided femoral nerve block with up to 20 mL of 0.3 mL.kg−1 of 0.5% bupivacaine and intravenous tramadol) and 16 patients (standard management group; up to 3 mL of 0.9% saline in the femoral sheath and intravenous tramadol). Tumor necrosis factor-α and visual analogue scale scores were evaluated immediately before the femoral nerve block and again at 4, 24, and 48 h after the femoral nerve block. All surgery was performed electively after 48 h of femoral nerve block. Results: The femoral nerve block group had a significantly lower mean tumor necrosis factor-α level at 24 (4.60 vs. 8.14, p < 0.001) and 48 h (5.05 vs. 8.56, p < 0.001) after the femoral nerve block, compared to the standard management group. The femoral nerve block group showed a significantly lower mean visual analogue scale score at 4 (3.63 vs. 7.06, p < 0.001) and 24 h (4.50 vs. 5.75, p < 0.001) after the femoral nerve block, compared to the standard management group. Conclusions: Ultrasound-guided femoral nerve block using 0.3 mL.kg−1 of 0.5% bupivacaine up to a maximum of 20 mL resulted in a significant lower tumor necrosis factor-α level.